The Influence of Performance Expectancy and Price Value on Favorable Behavioral Intentions Through Satisfaction With Viu Platform - Anzil Saputri; Erna Listiana; Barkah Barkah; Ana Fitriana (eCo-Buss, 2024)
The shift in video consumption from TV to online platforms is increasingly evident, especially among younger demographics who prefer streaming services such as Viu. The Viu platform's success is impacted by users' behavioural intention and perceived price value, which in turn influences user satisfaction and behavioural intention two essential characteristics Viu aims to attain and are critical to a technology's success. This research examines the impact of price value and performance expectancy on the behavioural intention and level of satisfaction of Viu users in Indonesia. This study employs quantitative data as its data type. This research is a causal associative study or cause and effect relationship. The data analysis approach used in this study is Structural Equation Modelling (SEM). Using quantitative methods and questionnaires as a medium for data collection, this study involved 206 respondents who are Viu users in Indonesia. The study's findings demonstrate the strong effect of price value and performance expectancy on satisfaction and favourable behavioural intentions. Satisfaction is a crucial mediator in strengthening the impact of price value and performance expectancy on favourable behavioural intentions.